An Important Indian Traditional Drug of Ayurveda Jatamansi and Its Substitute Bhootkeshi: Chemical Profiling and Antioxidant Activity. (21st March 2013) - Pandey, Madan Mohan; Katara, Antariksha; Pandey, Garima; Rastogi, Subha; Rawat, A. K. S.
Abstract : Nardostachys jatamansi DC. and Selinum vaginatum (Edgew) Cl. are two endemic high altitude Indian medicinal plants that have been traditionally known as "Jatamansi" and "Bhootkeshi, " respectively. These are used in various traditional herbal formulations and nutraceuticals, as well as to treat neurological disorders like epilepsy, hysteria, syncope, convulsions, and mental weakness. They resemble each other in their external morphological characters and characteristic odour, so their roots are often confused with each other. Since free radicals have been implicated in the pathogenesis of a considerable range of neurological disorders, including seizures and epilepsy, analysis of these two important medicinal plants was carried out based on their antioxidant activities and phenolic profiles. N. jatamansi expressed better antioxidant activity with both DPPH and TAC methods. Strong correlation was seen between TPC and antioxidant activities. Phenolic compounds such as chlorogenic acid, ferulic acid, protocatechuic acid, and syringic acid were analyzed qualitatively and quantitatively in the methanol extracts of N. jatamansi and S. vaginatum by HPLC. N. jatamansi was found to contain only protocatechuic and syringic acids while chlorogenic and ferulic acids were present only in S. vaginatum . The studies suggest that both of the plants exhibit distinctive properties and that their similar therapeutic uses may be dependent on synergistic effects exhibited by the different compounds present in them.